Le partage de l'Afrique et l'île d'Helgoland - Marcel, Gabriel (La Nature, 1890)
Keywords: Zanzibar

Le partage de la côte orientale d'Afrique - Marcel, Gabriel (La Nature, 1888)
Keywords: Zanzibar

Précis of correspondence relating to Zanzibar affairs from 1856 to 1872. Prepared by Captain P D Henderson, attached to the Foreign Department - Henderson, P. D. (British Library, 1872)
The file is a précis of correspondence related to affairs at Zanzibar between the years 1856 and 1872, prepared by Captain Philip Durham Henderson of the Foreign Department in the Government of India. The contents of the précis, which includes reports from Christopher Palmer Rigby, the British Consul at Zanzibar, and Sir William Marcus Coghlan, relate to: the death in 1856 of the Sultan of Muscat Syed Saeed [Sa‘id bin Sulṭān al-Sa‘id] without a direct heir; the succession struggle between Syed Thoweynee [Thuwaynī bin Sa‘id al-Sa‘id] and Syed Majid [Sa‘id Majid bin Said al-Sa‘id]; British arbitration in the dispute; succession arrangements at Muscat and Zanzibar; the slave trade between Zanzibar and Muscat. The précis is organised into six chapters (labelled I to VI), as follows: I – Events preceding the arbitration by the Government of India; II – Arbitration of the Government of India; III – Proceedings subsequent to the arbitration relating to the question of subsidy; IV – Events at Zanzibar from the arbitration to the death of Syed Majid; V – Events in Zanzibar from the death of Syed Majid; VI – Slave Trade. The contents page lists four appendices (labelled A to D) that are not included in this copy of the précis.
Genre: Archival file
Keywords: Zanzibar

Mr Rothery's report to the Treasury in respect to the Muscat subsidy and Zanzibar Agency Expenses - Moore, Adolphus Warburton (British Library, 1876)
A printed memorandum, written by Adolphus Warburton Moore, Assistant Secretary of the Political and Secret Department of the India Office, 27 September 1876. The memorandum discusses the views of Henry Cadogan Rothery on whether the Imperial Government had to contribute to the payment of an annual subsidy to the Sultan of Muscat (as compensation for the abandonment of his claims upon Zanzibar) and of the expenses of the Agency and Consulate at Zanzibar, made by the India Office from 1870. Rothery writes that, because the Agent at Zanzibar was also acting as Judge of the Vice Admiralty Court in the Trial of the Slave Trade cases, it was the duty of the Imperial Government to contribute towards these expences.
Genre: Archival file
Keywords: Zanzibar

Report of a committee on the Muscat subsidy and the Zanzibar Agency and Consulate - Mallet, Louis; Rothery, Henry Cadogan; Wylde, William Henry (British Library, 1876)
A printed report, written by a Committee formed by Louis Mallet, Henry Cadogan Rothery and William Henry Wylde, 8 December 1876. The Committee was nominated by H M's Treasury, the Secretary of State for Foreign Affairs and the Secretary of State for India, to determine whether the Imperial Government had to contribute to the payment of an annual subsidy to the Sultan of Muscat (as compensation for the abandonment of his claims upon Zanzibar) and of the expenses of the Agency and Consulate at Zanzibar, which had been paid by the India Office since 1870. The committee acknowledges that in 1873 it was agreed that these payments should be divided between Imperial and Indian Government, hence the Imperial Government had to compensate the India Office for the payments made in the years 1873-1877. The report includes a summary of payments made to the Sultan of Muscat between May 1873 and February 1877, expenses for the British Agency and Consulate General at Zanzibar for the period 1872-1877, and a proposed budget estimate for the future, to be equally divided between Imperial and Indian Government. Two declarations follow the report, from two comissioners in disagreement with the report.
Genre: Archival file
Keywords: Zanzibar

Memorandum No 1. Zanzibar Agency and Consulate Expenses - Moore, Adolphus Warburton (British Library, 1876)
A printed memorandum, written by Adolphus Warburton Moore, Assistant Secretary of the Political and Secret Department of the India Office, 17 August 1876. The first part of the document is a claim of expenses for an annual subsidy of 40,000 crowns from the Sultan of Zanzibar to the Sultan of Muscat as compensation for the abandonment of his claims upon Zanzibar, which was paid by the Political Agent at Muscat for the period 1870-1877, including a summary of payments made between May 1873 and February 1877. The second part of the document contains a claim for the expenses of the Agency and Consulate at Zanzibar, including: salary of Political Agent, Second Assistant and interpreters, furlough allowances and charge for interest on Government buildings.
Genre: Archival file
Keywords: Zanzibar

Navigation de l'île Bourbon à Zanzibar et à Pemba; position de ces îles exactement déterminée ; erreurs de route et de gisement qui se trouvent dans Horsburgh - Massieu de Clerval, Auguste Samuel (Annales maritimes et coloniales, 1822)
Keywords: Zanzibar

Anglo-German Treaty [Heligoland-Zanzibar Treaty] - Staatsarchiv (Sammlung der offiziellen Aktenstücke zur Geschichte der Gegenwart, 1891)
Keywords: Zanzibar

D'Aden a Zanzibar: un coin de l'Arabie heureuse le long des côtes - Roy, Alexandre Le (Alfred Mame et fils, 1899)
Keywords: Zanzibar

Socotra - Balfour, Bayley (Nature, 1880)
Keywords: Zanzibar

Documents sur l’histoire, la géographie et le commerce de l’Afrique orientale - Guillain, Charles (Bertrand, 1856)
Chapitre 19 : séjour à Zanzibar
Keywords: Zanzibar

The Exploration of Socotra - Sclater, P.L. (Nature, 1879)
Keywords: Zanzibar

Socotra - Sclater, P.L. (Nature, 1876)
Keywords: Zanzibar

Sidi Bargash Ben Saïd, sultan de Zanzibar - Armand, Paul; Marras, E. (Bulletin de la Société de géographie de Marseille, 1888)
Keywords: Zanzibar

Die Insel Socotra - Flückiger, F.A. (Archiv der Pharmazie, 1888)
Keywords: Zanzibar

Full-length seated portrait of Saiyid Majid, Sultan of Zanzibar - Chintamon, Hurrichund (1867)
Studio portrait of Saiyid Majid, Sultan of Zanzibar, seated beside a table with his arm resting on a large book, by Hurrichund Chintamon in the 1860s. This photograph is from the Archaeological Survey of India Collections and was shown at the 1867 Paris Exhibition. Sultan Sayyid Majid was born at Zanzibar in 1834, the sixth son of His Highness Sayyid Said bin Sultan, Iman of Muscat and Oman. Sayyid Majid was Governor of Zanzibar, Pemba and the East African domains during his father's reign. On the death of his father, 19 October 1856 he was proclaimed Sultan of Zanzibar and Oman. He died at Zanzibar 7 October 1870. 21.5 x 18 Centimetres. Photographer: Chintamon, Hurrichund.
Keywords: Zanzibar

Some account of the town of Zanzibar - Steere, Edward (Charles Cull, 1869)
Keywords: Zanzibar

Memoir on the Island of Socotra - Wellsted, James Raymond (Journal of the Royal Geographical Society of London, 1835)
Keywords: Zanzibar

Notes on Socotra - Hunter, F. M. (The Journal of the Anthropological Institute of Great Britain and Ireland, 1878)
Keywords: Zanzibar

Über den arabischen Dialekt von Zanzibar - Praetorias, Franz (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 1880)
Keywords: Zanzibar

[Letter from Rev. Dr. J.L. Krapf from East Africa, April 1853] - Krapf, J.L. (Journal of the American Oriental Society, 1854)
Keywords: Zanzibar

Note sur Zanzibar et la côte orientale d’Afrique - Germain, Adrien (Bulletin de la Société de Géographie, 1868)
Keywords: Zanzibar

Über die Religiösen Anschauungen der ibadhitischen Muhammedaner in Oman und Ostafrika - Sachau, Eduard (Mittheilungen des Seminars für Orientalische Sprachen an der königlichen Friedrich Wilhelms-Universität zu Berlin, 1899)
Based on chapters 27, 29 and 40 of Sirḥān b. Saʿīd al-Izkawī’s Kashf al-Ghumma.
Keywords: Zanzibar

Das Gutachten eines muhammedanischen Juristen über die muhammedanischen Rechtsverhältnisse in Ost-Afrika - Sachau, Eduard (Mittheilungen des Seminars für Orientalische Sprachen an der königlichen Friedrich Wilhelms-Universität zu Berlin, 1898)
The Arabic text and translation of an answer by Yaḥyà b. Khalfān b. Abī Nabhān al-Kharūṣī, Qāḍī of Zanzibar, to questions asked him about the relationship between Shāfiʿī and Ibāḍī jurisprudence in East Africa, and about the most important Ibāḍī and Shāfiʿī Fiqh books. Imbert 1903b, 19-21: an abstract of Sachau’s article. Yaḥyà b. Khalfān al-Kharūṣī was Qāḍī of Zanzibar and he answered to questions posed by Sachau [via Mr. Rössler].
Keywords: Fiqh; Zanzibar

Über eine arabische Chronik aus Zanzibar - Sachau, Eduard (Mittheilungen des Seminars für Orientalische Sprachen an der königlichen Friedrich Wilhelms-Universität zu Berlin, 1898)
Sachau indicates the parts in Ibn Ruzayq’s al-Fatḥ al-Mubīn that are (almost) copied from Kashf al-Ghumma.
Keywords: Zanzibar

Muhammedanisches Erbrecht nach der Lehre der ibaditischen Araber von Zanzibar und Ostafrika - Sachau, Eduard (Sitzungsberichte der Königlich Preussischen Akademie der Wissenschaften zu Berlin, 1894)
Critical analysis and translation of the chapters on the law of succession (ch. 61-77) and testament (ch. 58) in Abū ‘l-Ḥasan ʿAlī b. Muḥ. b.ʿAlī al-Basyāwī’s Mukhtaṣar al-Basyawī (Zanzibar 1886). See Guidi, Ignazio 1906 for an Italian translation. Imbert 1903b: an abstract of Sachau’s translation (9-12) and a comparison with chapter 21 of Thamīnī’s K. al-Nīl, translated by Zeys 1895 (12-19).
Keywords: Fiqh; Zanzibar

Geschichte des Araberaufstandes in Ost-Afrika. Seine Entstehung, seine Niederwerfung und seine Folgen - Schmidt, Rochus (Verlag der königlichen Hofbuchdruckerei Trowitsch und Sohn, 1892)
Keywords: Zanzibar

Suaheli-schriftstücke in arabischer schrift: mit lateinischer schrift umschrieben übersetzt und erklärt - Büttner, Carl Gotthilf (W. Spemann, 1892)
Keywords: Zanzibar

Handbook of British East Africa, including Zanzibar, Uganda, and the territory of the Imperial British East Africa company. - Foster (War Office, 1893)
Keywords: Zanzibar